A Review of Composite Materials - KLAAI, Lisa (Biopolymer Applications Journal, 2025)
Unlike conventional materials, composites have become an optimal option for a range of modern, industrial, clinical, and sports applications. This is combined with their noteworthy physical, thermal, electrical, and mechanical properties; the key concepts of composites are its physical properties, mechanical properties, tooling, design, inspection and repair. Military vehicles, such as airplanes, helicopters, and rockets, placed a premium on high-strength, light-weight materials. This review article attempts to give an overall outline of composite materials.